Normative values for sport-specific left ventricular dimensions and exercise-induced cardiac remodeling in elite Spanish male and female athletes - Boraita, A.; Díaz-Gonzalez, L.; Valenzuela, P. L.; Heras, M.-E.; Morales-Acuna, F.; Castillo-García, A.; Lucia, M. J.; Suja, P.; Santos-Lozano, A.; Lucia, A. (Sports Medicine - Open, 2022)
Key Points - The present study, which includes data from 3282 elite white athletes (mean age 23 ± 6 years, 37.8% women) of 46 different sports, suggests that the great majority (85.4%) of these athletes have normal LV geometry.